Plagiarism among Higher Education Students - Roman Yavich; Nitza Davidovitch (MDPI AG, 2024)
The problem of academic fraud has recently grown and includes plagiarism, the use of cellphones, copying from others, and writing by use of artificial intelligence (AI). The objective of this study was to examine the connection between academic dishonesty, class attendance, self-efficacy, and the use of digital tools. The study focused on higher-education students in Israel and included 121 participants. It was a mixed qualitative and quantitative study based on a structured questionnaire and on the previous literature. Studies showed that academic dishonesty increases when students fail to attend classes, have low self-efficacy, and attend classes remotely via communication platforms such as Zoom. In the current study, 50% of the participants reported that academic dishonesty was perceived as legitimate among their peer students. Preventive measures such as strengthening the students' self-efficacy during tests and other stressful situations and emphasizing the importance of acquiring professional knowledge and skills may more effectively eliminate fraud than the common method of disciplining wrongdoers.